9k+6=8k+

Simple and best practice solution for 9k+6=8k+ equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9k+6=8k+ equation:



9k+6=8k+
We move all terms to the left:
9k+6-(8k+)=0
We add all the numbers together, and all the variables
9k-(+8k)+6=0
We get rid of parentheses
9k-8k+6=0
We add all the numbers together, and all the variables
k+6=0
We move all terms containing k to the left, all other terms to the right
k=-6

See similar equations:

| 49=s+19 | | 180=4x+35 | | 7(8-8v)=6v-6 | | 5(3x+4)-2x=7x-3(-2+7 | | 16+14=-3(6x-10) | | 515x+20=x3x+4 | | 5x+6=2x36 | | 5x+6=2x36 | | x+x3+x4=24 | | 29-7x=28-22x | | 6x11/4=X | | 50x+750=25.5 | | 8x13=5x+20 | | 11+7.1n=8+7.4n | | 35-4x=7(5+5x) | | 5(t-9)+12t=20 | | 5y^2-220y=5y | | 5x5x=8x2x | | 3(2x+6)=-13+19 | | 0.50x+0.45X50=24.5 | | 6(1-8a)=138 | | (5t/9-3/4=1/12+5t/8) | | x/3+3/4=15/4 | | G=9/8(p-21) | | -3b+5(b+2)=4b(3b+5) | | -8w=15 | | -2(1y-1)=4y-(1y+2) | | -3x+9/3=9 | | P=100+0.03x | | 4.4+10m=8.27 | | 4.4+10m=7.32 | | 5(m+4)=-4(m+1)=16 |

Equations solver categories